THE ROLE OF JOB SATISFACTION AS A MEDIATION VARIABLE ON THE INFLUENCE OF WORK LIFE BALANCE, ISLAMIC WORK ETHICS AND BURNOUT ON TURNOVER INTENTION - Sukarman, Putri (UIN Salatiga, 2022)
This study aims to influence of work life balance, Islamic work ethics and burnout on employee turnover intention at PT Karya Toha Putra Semarang through job satisfaction as a mediating variable. This study uses quantitative methods by processing primary data through a questionnaire given to 104 respondents to the employee of PT Toha Karya Putra Semarang. Purposive sampling technique in sampling. The data was collected using a questionnaire and the data was processed using SPSS 26. Data analysis in this study used the classical assumption test, hypothesis test and path analysis test. The results showed that work life balance had a significant and negative effect on turnover intention, Islamic work ethics had a significant and positive effect on turnover intention, burnout had a significant and positive effect on turnover intention, work life balance had a significant and positive effect on job satisfaction, Islamic work ethics had an effect significant and positive on job satisfaction, burnout has a significant and negative effect on job satisfaction, job satisfaction has a significant and negative effect on turnover intention, job satisfaction is able to mediate the effect between work life balance and turnover intention, job satisfaction is able to mediate the influence between Islamic work ethics with turnover intention, job satisfaction is able to mediate the influence between burnout and turnover intention. Keywords: Work Life Balance, Islamic Work Ethics, Burnout, Job Satisfaction, Turnover Intention